(untitled) (Research, Society and Development, 2022)
Objective: to investigate the judgment of children regarding the use of parameters of oral expression in reading aloud in moments before and after speech-language pathology intervention. Methodology: this is a prospective intervention study carried out in two stages. In the first one, two teachers participated in a workshop in which the resources of oral expressiveness in reading aloud were worked, such as pause, articulation, resonance, pitch, loudness and breathing with a focus on pneumophonoarticulatory coordination. Before and after this intervention, audio-recorded material from the reading aloud of the same text was collected for further analysis. In the second part of the research, this material was presented to 54 children (5 and 6 years old) and an analysis was carried out in the light of an auditory perceptual assessment. Of the children who noticed the difference, all opted for the post-intervention reading and were gathered in small groups to justify their choices. Results: there was a statistically significant association between the condition heard. In the justifications for their choices, there was an association sometimes with meaning, sometimes with sound. After quantifying the occurrences, it was found that the expressive effects adopted by the teachers were more associated with the meaning of the voice (40) than with the sound (26). Conclusion: children were able to perceive differences in oral expressiveness highlighted more by expressions related to meaning.